Non-indigenous macrozoobenthic species on hard substrata of selected harbours in the Adriatic Sea. (October 2019) - Spagnolo, A.; Auriemma, R.; Bacci, T.; Balković, I.; Bertasi, F.; Bolognini, L.; Cabrini, M.; Cilenti, L.; Cuicchi, C.; Cvitković, I.; Despalatović, M.; Grati, F.; et al.
Abstract: The intense shipping traffic characterising the Adriatic Sea favours the spread of marine organisms. Yet, a study of 12 Adriatic ports (4 on the western side and 8 on the eastern side of the basin) found that non-indigenous species (NIS) accounted for only 4% of the benthic communities settled on hard substrates. The cirripeds Amphibalanus amphitrite and Balanus trigonus, found in 8 harbours, were the most common invaders followed by Amphibalanus eburneus, the ascidian Styela plicata, and the bivalve Magallana gigas . The highest percentage of NIS was recorded in Venice and Ploče, the harbours with the least rich native communities; the lowest percentage was retrieved in Trieste, Koper, Pula, and Rijeka, the harbours hosting the highest species diversity. In contrast, the ports of Bari and Ancona showed both high NIS percentages and highly diversified communities. Highlights: Harbours represent a suitable receptacle for non-indigenous species (NIS). Fouling macrobiota were investigated from twelve western and eastern Adriatic ports. Highest percentages of NIS were obtained where total Richness was low. Biotic and abiotic factors are crucial in defining the vulnerability to invasibility.